(De)Humanizing Humor: The Anthill of Life and Politics in the Theatre of Sabina Berman - Priscilla Meléndez (Studies in 20th & 21st Century Literature, 2008)
This article examines several theatrical works of this Mexican dramatist by means of ironic humor as a powerful resource to examine the nature of human communication, and to expose the serious and devastating social and political aspects of contemporary culture: machismo, political corruption, sexual violence, sexism, exploitation, historical manipulation, and hopelessness. In a tense environment where humor might not seem appropriate, Berman masterfully uses and critically examines it as a means to understand humor’s serious implications and its comic imperfections, as she subtly recurs to but also parodies some of the most recognized theories of humor. Berman’s use of incongruity highlights the tension in her theatrical production, in which even the most sordid acts are counterbalanced by irony, which produces not only surprise or pain in the face of the unexpected, but also pleasure. Perhaps that is why she incorporates the image of the anthill in her reflections about society, politics, history, sexuality, gender identity, and art, where the artist, with her double perspective, like the queen of the “Formicas exsectoides,” is able to interpret the world from both the inside and the outside.
Keywords: Mexican; humor; communication; contemporary culture; machismo; political corruption; sexual violence; sexism; exploitation; Sabina Berman; anthill; society; politics; sexuality; formicas exsectoides